miRNA Dysregulation in the Development of Non-Alcoholic Fatty Liver Disease and the Related Disorders Type 2 Diabetes Mellitus and Cardiovascular Disease - López-Pastor, Andrea R.; Infante-Menéndez, Jorge; Escribano, Óscar; Gómez-Hernández, Almudena (Frontiers in Medicine, 2020)
According to the World Health Organization, the continuing surge in obesity pandemic creates a substantial increase in incidences of metabolic disorders, such as non-alcoholic fatty liver disease (NAFLD), type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). MicroRNAs (miRNAs) belong to an evolutionarily conserved class of short (20–22 nucleotides in length) and single-stranded non-coding RNAs. In mammals, miRNAs function as critical post-transcriptional negative regulators involved not only in many biological processes but also in the development of many diseases such as NAFLD and comorbidities. More recently, it has been described that cells can secrete miRNAs in extracellular vesicles (ECVs), transported by body fluids and uptaken by other tissues regulating gene expression. Therefore, this could be a mechanism of signaling involved not only in physiological pathways, but also in the development of diseases. The association of some miRNA expression profiles with certain disorders has made them very interesting molecules for diagnosis, prognosis and disease management. The finding of specific miRNA signatures to diagnose NAFLD and related diseases could anticipate the risk of development of related complications and actually, it is the driving force of the present health strategies worldwide. In this review, we have included the latest advances in the knowledge about the miRNAs involved in the development of NAFLD and related diseases and examined how this knowledge could be used to identify new non-invasive biomarkers and new pharmacological interventions.